Improving the Light Fastness of the Wool Dyed with Pomegranate Peels - Zehra Gözütok; M. İbrahim Bahtiyari (Journal of Natural Fibers, 2022)
Natural dyes are highly promising alternatives; however, their use has some drawbacks such as low light fastness, color yield, and repeatability. The objective of this study is to improve the light fastness of natural dyes. For this objective, wool fabrics dyed with pomegranate peels were subjected to different chemical treatments and UV curing. An important conclusion of this work is that UV curing can significantly increase the light fastness of the fabrics dyed with pomegranate peels. Moreover, different chemical processes including optical brightening have exhibited a positive effect on the light fastness of the samples. As an example, UV light exposure of the fabric, which was mordanted with copper sulfate and treated with TiO2, resulted in an increase of the light fastness from 4–5 to 7.